Conformational transition in SPR experiments: impact of spacer length, immobilization mode and aptamer density on signal sign and amplitude. Issue 19 (19th August 2022) - Pons, Marina; Perenon, Marine; Bonnet, Hugues; Gillon, Emilie; Vallée, Celio; Coche-Guérente, Liliane; Defrancq, Eric; Spinelli, Nicolas; Van der Heyden, Angeline; Dejeu, Jérôme
Abstract : The spacer length and immobilization mode impact the Surface plasmon resonance (SPR) signal and affinity measured for small target/aptamer recognition. The signal could be positive, negative or null explained by refractive index increment deviation. Abstract : Surface plasmon resonance (SPR) is an optical, real-time and label-free technique which represents a standard to study biomolecular interactions. While SPR signals are usually positive upon recognition, a few cases of negative signals have been reported because of significant conformational transition of the receptor upon the recognition of the target. In this study, we reported on the observation of negative or null SPR signals for an aptamer recognition with its low molecular weight target. The introduction of a spacer group for the aptamer immobilization led to a null SPR signal despite the device sensitivity and effective target recognition (a K D around 200 nM as demonstrated using a quartz crystal microbalance with dissipation monitoring and isothermal titration calorimetry). We demonstrated that this unconventional signal could be attributed to two opposite contributions: a positive one is afforded by the aptamer recognition and folding whereas a negative one results from the refractive index increment (RII) deviation upon the formation of the complex (ligand/analyte). We also demonstrated that the RII deviation is sensitive to the modification of the sequence flexibility and therefore depends on the anchoring procedure and the spacer length between the anchoring function and the site of recognition.